The Art of Writing Place. Issue 10 (October 2014) - Ward, Miranda
Abstract This paper provides an overview of recent work by academic geographers who use creative approaches to writing, both structurally and linguistically, to explore and advance themes relating to space and place. It places this work in the context of other contemporary engagements with creative practices in cultural geography and sets out some of the possibilities for, as well as the challenges associated with, a "creative‐critical" approach to writing geography. It outlines several ways in which this approach can help cultural geographers engage with certain ideas about place through a focus on three particular themes: (1) the idea of place as something fluid and always‐becoming; (2) the relationship between the body and place; and (3) the spatiality of text.